Economic Efficiency of Rice Farming: A Performance Difference among Agricultural Insurance Participant and Non-participant Farmer - Eva Helmy; Lies Sulistyowati; Trisna Insan Noor; Iwan Setiawan (AGRARIS: Journal of Agribusiness and Rural Development Research, 2023)
Agricultural insurance is a risk-sharing business arrangement to protect farmers who encounter problems with adverse selection and moral hazards caused by asymmetric information. This situation leads to market inefficiencies since people with more information commonly take advantage of less informed people. This study aimed to compare the performance difference in the economic efficiency of rice farming between Rice Farming Insurance (RFI) participants and non-participant farmers. Primary data were collected from 202 farmers in Tangerang Regency. The marginal value product–marginal factor cost (MVP-MFC) approach was utilized to estimate resource use efficiency in rice production. The t-test was applied to determine differences in input allocation. The MVP-MFC discovered that the use of seeds was efficient for RFI participant farmers. Meanwhile, land, organic fertilizer, and pesticide had not been efficient, and inputs of inorganic fertilizer and labor were inefficient. Conversly, non-participant farmers indicated that the use of land, seeds, organic fertilizers, and pesticides had not been efficient, but the use of inorganic fertilizers and labor was inefficient. However, the comparison test revealed no difference in the input allocation efficiency between RFI participants and non-participant farmers. Hence, innovation in media and extension methods were required to change farmers’ behavior. Government policies were also necessary to ensure the availability of inputs. In addition, avoiding adverse selection and moral hazards in agricultural insurance was required to identify hazardous groups.